UNIFORM STRUCTURES WITH CONTRACTIVE MAPPINGS AND PRODUCT OF FUZZY METRIC SPACES - AbdulGawad A. Q. Al-Qubati (European Scientific Journal, ESJ, 2013)
According to the notion of a fuzzy metric due to George and Veeramnai, we study and extends some topological Properties to fuzzy metric spaces such as uniform continuity- uniformly convergence – equicontinuous sequences of functions, also some topological properties for product of fuzzy metric spaces with contractively and fixed point theorem are studied , some important and interesting results of their properties are obtained.